Comparative analysis of the feeding habits of Rapana venosa and Neptunea arthritica cumingii near Zhangzi Island, China, based on stable isotope ratios and fatty acid profiles. (13th December 2020) - Yang, Mei‐Jie; Feng, Jie; Yu, Zheng‐Lin; Song, Hao; Hu, Zhi; Zhou, Cong; Shi, Pu; Zhang, Tao
Abstract: The two whelks Rapana venosa and Neptunea arthritica cumingii are important fishery resources, but the biomass of these species has declined extensively over the years. In the present study, we selected the sea area around Zhangzi Island, a typical North China Sea island, as the study area. Biochemical trophic markers (stable isotopes and fatty acids (FAs)) were used to estimate the dietary compositions of R. venosa and N. arthritica cumingii . The combined use of stable isotope analysis and analysis of FA composition enabled a comprehensive investigation of these species in the North China Sea. The results showed that the two whelk species were significantly distinguished by their FAs, suggesting that dietary composition significantly differs between the two species; however, the values of C22:6(n‐3) (DHA)/C20:5(n‐3) (EPA) and δ 15 N indicated no significant difference between the two whelk species at the trophic level. The EPA content of N. arthritica cumingii was higher than that of R. venosa, indicating that the former species is more involved in the scavenger food chain, although this FA species represented a small proportion of the dietary composition in both whelk species. In contrast, there were no significant differences in stable isotope ratios or FA contents among different size classes of the same whelk species. This study provides insight into the structural changes and dynamics of marine communities. Such information is essential for the protection of fishery resources, their sustainable development and utilization, and the scientific management of marine ecosystems.